2016
DOI: 10.1038/ncomms13564
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing radiation tolerance by controlling defect mobility and migration pathways in multicomponent single-phase alloys

Abstract: A grand challenge in material science is to understand the correlation between intrinsic properties and defect dynamics. Radiation tolerant materials are in great demand for safe operation and advancement of nuclear and aerospace systems. Unlike traditional approaches that rely on microstructural and nanoscale features to mitigate radiation damage, this study demonstrates enhancement of radiation tolerance with the suppression of void formation by two orders magnitude at elevated temperatures in equiatomic sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
230
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 638 publications
(246 citation statements)
references
References 39 publications
11
230
2
3
Order By: Relevance
“…(Yang et al, 2018). Unlike in Lu et al (2016b), no voids have been observed in both cases at all the test temperatures. For the observable defect clusters, the density decreases but the size increases with increasing irradiation temperature (Kumar et al, 2016;Yang et al, 2018).…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 68%
See 3 more Smart Citations
“…(Yang et al, 2018). Unlike in Lu et al (2016b), no voids have been observed in both cases at all the test temperatures. For the observable defect clusters, the density decreases but the size increases with increasing irradiation temperature (Kumar et al, 2016;Yang et al, 2018).…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 68%
“…FIGURE 7 | Cross-sectional TEM images for the void distributions in (a) Ni and (b) NiCoFeCr, and elemental distribution around (c) dislocations and (d) voids in NiCoFeCr, after 3 MeV Ni ion irradiations at 500 • C. Adapted from Lu et al (2016b) and Lu et al (2017). (Yang et al, 2018).…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a new class of materials, these compositionally complex alloys have attracted a large number of research interests over the past decade, leading to the discovery of some excellent mechanical properties and interesting physical properties [3][4][5][6][7][8][9][10]. Recently, many multicomponent solid solution alloys with 3d transition elements from Cr to Ni in the periodic table, which have similar atomic size, have been synthesized and all of these Ni-based alloys have a simple face-centered cubic (fcc) structure [10][11][12][13][14].…”
mentioning
confidence: 99%